The effect of seaweed Ecklonia maxima extract and mineral nitrogen on fodder grass chemical composition - Ciepiela, Grażyna Anna (Environ Sci Pollut Res Int, 2015)
The objective of this study was to determine the effect of the biostimulant Kelpak and different nitrogen rates on cellulose, hemicellulose and lignin contents as well as non-structural carbohydrates in orchard grass and Braun’s festulolium. The experiment was a split-plot arrangement with three replicates. It was set up at the experimental facility of the University of Natural Sciences and Humanities, Siedlce, in late April 2009. The following factors were examined: biostimulant with the trade name Kelpak SL applied at 2 dm(3) ha(−1) and a control—no biostimulant; nitrogen application rates 50 and 150 kg ha(−1) and a control (0 kg ha(−1)); pure stands of grass species grown in monoculture—orchard grass (Dactylis glomerata), cv. Amila,—Braun’s festulolium (Festulolium braunii), cv. Felopa. Kelpak significantly increased non-structural carbohydrates, and increasing nitrogen rates reduced the concentration of these components in plants. Increasing nitrogen rates significantly decreased cellulose, hemicellulose, lignin and non-structural carbohydrate contents. Compared with orchard grass, Braun’s festulolium proved to be of a higher nutritional value due to lower cellulose, hemicellulose and lignin contents and more non-structural carbohydrates. The aforementioned contents in the grasses differed significantly depending on the cut. Most cellulose and non-structural carbohydrates were determined in second-cut grass whereas most hemicellulose and lignin in second-cut grass.